Exchange Rate Variation And The Agricultural Output In Pakistan: A Time Series Analysis - Shah, Mukamil; Ali, Sher; Sami, Fariha (Migration Letters, 2024)
This study investigates the impact of the real effective exchange rate on the agricultural sector in Pakistan. For empirical analysis, quarterly data covering the period 2007Q1-2021Q4 is used. Based on the unit root test, the long-term relationship between the real effective exchange rate, agricultural output, agricultural imports, and agricultural exports is estimated through the Johansen cointegration approach. A Vector Error Correction Mechanism (VECM) is used for short-term relationships between the real effective exchange rate, agricultural output, agricultural imports, and agricultural exports. Study findings reveal that the real effective exchange rate (REER) and agricultural exports have positive impacts on Pakistani agricultural output in the long run. While there is a negative relationship between agricultural output and agricultural imports in Pakistan. The State Bank of Pakistan should focus on the most appropriate exchange rate policy so that agricultural output thereby boosting agriculture exports. An increase in agriculture exports would raise the national output on one hand and it is a source of foreign exchange earnings on the other.